Language Verbalization of Quantitativeness in Modern Mass Media: Linguistic-cognitive and Communicative-pragmatic Dimensions in Ukrainian Language - Kostusiak, Nataliia M.; Shulska, Nataliia M.; Lisova, Yuliia; Yaresko, Kateryna; Ivanova, Iryna; Pochuieva, Olha; Afanasieva, Olena (My University, 2023)
Quantitativeness is described in the article as a generalized linguistic concept of cognitive and communicative-pragmatic direction, which is characterized by an internal meaning structure and a system of specialized and transposed different-level linguistic means. The focus on content priority, in particular on the set of deep semantic invariants, ensured quantitativeness analysis in several aspects: 1) in view of thought-speech activity and the basic principles of functional-categorical grammar, which served as a basis for distinguishing predicative, substantive, adjectival, and adverbial quantitativeness; 2) on the axis of quantitative certainty – quantitative uncertainty; 3) in the context of concepts many – few (багато – мало) with their various modifications – from too much to too little quantity; 4) in the plane of the ascending or descending manifestation of the sign in one subject compared to another (others) or in the same one, but at different times, which corresponds to the pattern of more (greatest) – less (least) (більше (найбільше) – менше (найменше)); 5) with an emphasis on the totality of means of expression. Verbs, numerals and their semantic correlates, in particular nouns, numeral-noun compounds, and phraseological units are distinguished among language units with a generalized quantitativeness scheme. It was found that a significant part of these markers serves as a bright emotional expressive tool, aimed not only at verbalizing media texts, but also at expressing a mocking- ironic tone. The focus on modern language practice led to the selection of quantitatively labeled compounds associated with destructiveness. However, such violations of the language standard are recognized as justified, as they perform an important stylistic and communicative-pragmatic role. The units expressing language dynamics include spliced words, lexemes, the semantic structure of which has shifted, as well as nominations formed by morphological methods. It is emphasized that the appearance of additional negative connotations is characteristic of most of them. It is noted that the active interaction of the language of the mass media and oral communication is indicated by words of narrow stylistic purpose (with figurative meaning, jargonisms, slangisms, etc.), which explicate an indefinite amount and at the same time give general expression and a peculiar flavor to the expression.
Keywords: quantitativeness; media linguistics; cognitive and communicative-pragmatic dimensions; vocabulary; evaluative and emotional expressive means; slangisms; Ukrainian language; parts of speech; mass media